Search for heavy Higgs bosons with flavour-violating couplings in multi-lepton plus b-jets final states in pp collisions at 13 TeV with the ATLAS detector. (Tufts University. Tisch Library., 2024)
Keywords : Beyond Standard Model, Exotics, Hadron-Hadron Scattering.; Springer Open.